PENGGUNAAN MEDIA -AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI SISWA BELAJAR MUSIK ANSAMBLE KELAS VIII-A SMP NEGERI 15 KOTA TASIKMALAYA - Fatimah, Fatimah (LPPM Universitas Bina Bangsa, 2023)
Learning media in the form of books, radio broadcasts, recorded events, films, computers, and television have the potential to grow and develop learning communities. Therefore, every teaching and learning activity to achieve educational goals, the use of media cannot be ignored. Teacher is a career position. Functional and professional, a member of the community who is competent (capable, able and authorized) and gains the trust of the community and/or government to carry out the duties, functions and roles and responsibilities of teachers, both in school-line educational institutions and out-of-school institutions. Teachers who have not mastered learning will be left behind by the flow of information and communication developments. A creative alternative for that is learning that is able to balance the work of the left and right hemispheres of the brain. The left brain plays an important role in the processing of logic, words, mathematics and sequences or what is known as the brain related to academic learning. While the right brain is related to rhythm, music, pictures, colors, space and imagination or what is known as the brain which is related to creative activity. The combination of the work of the two hemispheres in a lesson is what can reproduce the creativity of mastering learning concepts. The proper implementation of learning media for this is